"I'm a sociologist too, right?" Cinema and the representation of contemporary violence in Spain. Issue 2 (October 2021) - Sorogoyen, Rodrigo; Ferret, Jérôme
The Spanish director's oeuvre offers a unique vision of the various forms of violence at work in contemporary Spanish society. This study aims to encourage social scientists to reflect on their own practice and identify potential blind spots in their work. More broadly, the young Spanish director's output can be viewed as the product of a particular socialization (both familial and academic) and his belonging to a generation uninhibited by the codes of classic Spanish politics. In this sense, his is a "post 15-M1 cinema, " part of a "second transition." These are the factors that must inform a sociological interpretation of three of his most representative works, and the reading of the interview that follows.